Comparing outcomes after peripheral nerve block versus general anesthesia for lower extremity amputation: a nationwide exploratory retrospective cohort study in Japan. Issue 6 (June 2020) - Abe, Hiroaki; Sumitani, Masahiko; Matsui, Hiroki; Aso, Shotaro; Inoue, Reo; Fushimi, Kiyohide; Uchida, Kanji; Yasunaga, Hideo; Yamada, Yoshitsugu
ABSTRACT : Background and objectives : The health benefits of peripheral nerve block (PNB) on postoperative complications after lower extremity amputation (LEA) compared with general anesthesia (GA) remains controversial. We performed a retrospective propensity score‐matched cohort analysis to compare major outcomes after LEA with PNB versus GA. Materials and methods : We used a nationwide inpatient database in Japan to compare patient outcomes after LEA with PNB versus GA from 2010 to 2016. Our primary outcome was 30‐day mortality after LEA. The incidence of composite morbidity from life‐threatening complications and of delirium within 30 days after LEA were secondary outcomes. We conducted propensity score‐matched analyses of patients who underwent below knee or foot amputation using 36 covariates. Logistic regression analyses fitted with generalized estimating equations were performed to calculate ORs and their 95% CIs. Results : Of 11 796 patients, 747 received PNB and 11 049 received GA. After one‐to‐four propensity score matching, 747 patients were included in the PNB group and 2988 in the GA group. The adjusted ORs for postoperative mortality, composite morbidity and delirium within 30 days after LEA were 1.11 (95% CI 0.75 to 1.64), 1.15 (95% CI 0.85 t o1.56) and 0.75 (95% CI 0.57 to 0.98), respectively, for the PNB group with reference to the GA group. Conclusions : There was no significant difference between groups in 30‐day mortality or composite morbidity. The PNB group showed a significantly lower risk of postoperative delirium than the GA group. Our findings suggest that PNB may have advantages over GA in preventing postoperative delirium among patients undergoing LEA.